Academic psychological capital questionnaire 12 (APCQ-12): psychometric validity and measurement invariance in a Chilean sample of high school students - Carmona-Halty, Marcos; Sepúlveda-Páez, Geraldy; Semir-González, Carla; Alarcón-Castillo, Karina; Mena-Chamorro, Patricio (Frontiers in Psychology, 2023)
The present study evaluated the psychometric properties of the Academic Psychological Capital Questionnaire 12 (APCQ-12) in a sample of 2196 Chilean high school students (51 % girls) aged 12 to 17 years (mean 14.83 years). Results showed that:(1) the APCQ-12 produces adequate scores in terms of reliability; (2) the internal structure of the questionnaire obtains adequate fit indices, for a second order model, which is consistent with previous research; and (3) the APCQ-12 proved to be sex and age invariant.Overall, the APCQ-12 proved to be an adequate questionnaire for measuring academic psychological capital in Chilean high school students, producing valid and reliable scores.